Między kulturą wysoką a kulturą popularną. O muzyce George'a Gershwina w „Manhattanie” Woody'ego Allena - Pomostowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Between high culture and popular culture. The music of George Gershwin in Manhattan by Woody Allen The article focuses on the relationships between high culture and popular culture in relation to film music. To this end, the author conducted a thorough analysis of the works of George Gershwin used in Woody Allen’s film Manhattan. The article consists of two parts and a conclusion. In the first part, the author presents a brief history of the continuous grinding together of high and popular culture in music, resulting in symphonic jazz, which came about in the 1920s, and whose precursor was George Gershwin. The second part is a cinematic and musicological analysis of all the works of Gershwin appearing on the soundtrack of Manhattan, and an attempt to find associations between the director and composer. In conclusion, the author notes that the phenomenon of mixing of popular culture and mass culture (both on the music, as well as its use in the work of the film) is subordinated in both George Gershwin and Woody Allen’s work to attempts to find their own identity, and one of the sources of inspiration of both artists is the same New York City, which is a city-myth.